2019
DOI: 10.1111/ppe.12596
|View full text |Cite
|
Sign up to set email alerts
|

Associations of prenatal or infant exposure to acetaminophen or ibuprofen with mid‐childhood executive function and behaviour

Abstract: Background: Over-the-counter analgesics during pregnancy or infancy may be related to neurobehavioural problems in children, but little is known about effects of different analgesic types, dosage, and timing.Objectives: Examine associations of acetaminophen and ibuprofen use during pregnancy and infancy with executive function and behaviour problems in children. Methods:We included 1225 mother-child pairs from Project Viva, a pre-birth cohort study. We assessed prenatal acetaminophen and ibuprofen use in early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 38 publications
(55 reference statements)
0
49
0
Order By: Relevance
“…Given that all exposure collected in the included studies involved some degree of recall, with latency ranging from weeks to years, some degree of misclassification is inevitable. Further, several studies included self‐reported exposure and outcome data from the same source (ie maternal report), which may leave them vulnerable to dependent measurement error. If over‐reporting of exposures co‐occurs with over‐reporting of outcomes, for example, this could produce the appearance of a strong effect of exposure on outcome.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Given that all exposure collected in the included studies involved some degree of recall, with latency ranging from weeks to years, some degree of misclassification is inevitable. Further, several studies included self‐reported exposure and outcome data from the same source (ie maternal report), which may leave them vulnerable to dependent measurement error. If over‐reporting of exposures co‐occurs with over‐reporting of outcomes, for example, this could produce the appearance of a strong effect of exposure on outcome.…”
mentioning
confidence: 99%
“…If over‐reporting of exposures co‐occurs with over‐reporting of outcomes, for example, this could produce the appearance of a strong effect of exposure on outcome. Several studies addressed this by using multi‐informant ascertainment, such as including reports from both the parent and a teacher, or including a clinical evaluation of neurodevelopment . In two studies, parent and teacher reports diverged, but in a third they did not, making this difficult to interpret.…”
mentioning
confidence: 99%
See 3 more Smart Citations